The Ubuntu concept, sexual behaviours and stigmatisation of persons living with HIV in Africa: A review article - Elvis Enowbeyang Tarkang; Lilian Belole Pencille; Joyce Komesuor (AOSIS, 2018)
Stigma and discrimination and risky sexual behaviours have been major stumbling blocks to the efforts by implementers to mitigate the effects of HIV amongst communities in Africa. A key cultural resource, based on evolving South African cultural traditions, is the notion of Ubuntu, which is grounded in respect, ethics, humanity and the interconnectedness of beings. This concept can be a useful resource in upholding confidentiality, a central requirement in research ethics and the deliverance of health promotion interventions regarding HIV/AIDS. This article explored the applicability of the Ubuntu concept in enhancing safe sexual practices and positive attitudes towards persons living with HIV, with the view of achieving Zero new infections, Zero discrimination against persons living with HIV (PLHIV), and Zero AIDS-related deaths. A review of literature was undertaken. Electronic databases, academic journals and books from various sources were accessed. Several key search terms relating to the tenets of Ubuntu, stigma and discrimination towards PLHIV, and sexual behaviours were used. Only references deemed useful from relevant texts and journal articles were included. Going therefore by the Ubuntu tradition of basic respect and compassion for others, one will expect positive attitudes towards PLHIV. This review therefore advocates positive attitudes towards PLHIV. Also, according to the Ubuntu tradition that prescribes a rule of conduct and social ethics, one would expect the sexual behaviours of youths in Africa to be good. This review article also advocates safe sexual behaviours of adolescents in Africa. With this in mind, from a critical Ubuntu-centric philosophical perspective, this article breaks new ground by advocating the use of the Ubuntu concepts in enhancing safe sexual practices and positive attitudes towards PLHIV in Africa. This could in turn bring about safe sexual practices among youths, and curb the discrimination and stigmatization against PLHIV in Africa.